How liquidity and solvency affect stock prices. Does profitability really matter? Evidence from Indonesia - Purbasari, Intan (Eastasouth Institute, 2024)
The purpose of this study is to investigate the relationship between the variables shown in the conceptual model, with an emphasis on the role that profitability plays as a mediator in the relationship between stock prices, liquidity, and solvency. Secondary data from financial statements and stock summaries of businesses listed on the IDX are used in this quantitative research project. According to the findings, profitability and solvency both had a significant impact on stock prices, but liquidity had no appreciable effect.